MEDIA PEMBELAJARAN PENDIDIKAN GURU MADRASAH IBTIDAIYAH (PGMI) - RORA RISKY WANDINI (Universitas Islam Negeri Sumatera Utara, 2016)
Learnig is an activity that inovlves a person in an attempt to acquire the knowledge, skill and positive values by untilizing a variety of sources for learning. In implementing learning mi prospective teachers must pay attention to a series of learning design. The rule on from of learning design is able to support the knowledge and learning styles of learners